Severe insulin resistance: pathologies. (20th July 2017) - Melvin, Audrey; Stears, Anna
Abstract: In parallel with the increasing prevalence of obesity, rates of insulin resistance and its associated complications have increased; however, insulin resistance is not only a disease of the overweight and obese. Disorders of adipose tissue expandability and insulin receptor signalling cause syndromes of severe insulin resistance that may go unrecognised in clinical practice but whose metabolic complications are significant and often the initial presentation of the condition. This review will discuss the differing pathologies mediating insulin resistance that may be seen in clinical practice and will outline the phenotypic characteristics that may allow their differentiation. Copyright © 2017 John Wiley & Sons.